Representation of Self and Reincarnation Among the Dene-Tha - Goulet, Jean-Guy (Culture, 1988)
Dreams and visions are conceived by the Dene-tha of northwestern Alberta as "ways of knowing with the mind". In particular, dreams and visions are a means through which the spirits of deceased persons may be encountered and observed. In some cases the spirit of the deceased is "seen" or "known" to enter a woman’s body to reincarnate as a child. This "knowledge" determines the way in which Dene-tha represent themselves to themselves and to each other. The purpose of this paper is to describe and analyze the Dene-tha representation of self as reincarnated individual. Thus, the paper draws the implications for an anthropological understanding of dreams, visions, and self among an aboriginal population.